Probing the morphology and anti-organic fouling behaviour of a polyetherimide membrane modified with hydrophilic organic acids as additives - Hebbar, Raghavendra S. (Royal Society of Chemistry, 2015)
A facile approach for the preparation of an organic antifouling polymer membrane has been developed using low molecular weight organic acids as additives. The presence of these additives in the membrane was analysed by FTIR spectroscopy. The properties of the modified membranes were investigated in terms of contact angle, water uptake capacity, SEM and AFM analysis. These additives exerted a strong impact on the rheological properties of the casting solution, thereby altering the membrane morphology, surface roughness, water flux and the hydrophilicity of the membranes, as compared to those of the pristine polyetherimide (PEI) membrane. The organic antifouling properties of the modified membrane were analysed by filtering both bovine serum albumin (BSA) and humic acid solutions. The results showed that the additives exhibited a remarkable improvement in the antifouling properties (FRR of 72%) and a humic acid rejection of up to 86%. These outcomes offer new insights into the use of cheaper and readily available organic acids as additives, compared to the traditional, synthetic polymer materials as additives in membrane preparation.